Respuesta :

Answer:

f(5) = 22

Step-by-step explanation:

Given: f(X) = (3x + 4) -(2 -x)

To find f(5) replace x by 5 in the above expression, we get

f(5) =(3*5 + 4) - (2 - 5)

f(5) = (15 + 4) -(-3)

f(5) = 19 + 3

f(5) = 22

Hope this will helpful.

Thank you.

Hello!

The answer is: [tex]f(5)=22[/tex]

Why?

Evaluating a function means that the variable (x in this case) will be replaced with the given value (5). So, where we have the variable "x" we should change it for the number 5.

So, evaluating we have:

[tex]f(x)=(3x+4)-(2-x)\\f(5)=(3*5+4)-(2-5)\\f(5)=15+4-(-3)\\f(5)=19+3\\f(5)=22[/tex]

Have a nice day!